KEDUDUKAN HAK CIPTA SEBAGAI OBJEK WAKAF DAN AKIBAT HUKUMNYA - Andi Santri Syamsuri (Muhammadiyah Makassar University, 2023)
ABSTRACTWaqf is an activity of giving a cash or non-cash asset in order to generate more benefits for others. Waqf objects that can be donated are movable or immovable objects that are immovably owned. Article 15 to Article 22 of government regulation Number 42 of 2008 regarding the implementation of Law Number 2004 concerning waqf. Especially for movable objects other than money, in this case Intellectual Property Rights, is regulated in Article 21 paragraph b of Government Regulation 42 of 2008 which states that copyright is one of them. In Law Number 28 of 2014 concerning Copyright, it stipulates that copyright is a right that contains moral rights and economic rights. Specifically for moral rights, Article 5 paragraph 2 of the Copyright Act stipulates that moral rights cannot be transferred as long as the creator is still alive. If the rights inherent in copyright cannot be transferred, then is the copyright waqf still valid according to law? What are the legal consequences that arise in the practice of copyright waqf? The method used in this paper is normative juridical and descriptive-comparative research specifications. The aim is to carry out an analysis related to applicable laws and regulations by comparing them with the view of Islamic law. Data was collected through literature study, then analyzed using qualitative normative methods. The conclusion is that Copyright remains legal as a waqf object because the law does not require the transfer of all benefits to waqf but only a part of it, both physical and functional as long as it does not lose the economic value of its benefits. Then, when viewed from the various types of copyright, there are several types that cannot be donated unconditionally, due to contradictions with several fatwas of the scholars who forbid both haram substance and haram function.As for the legal consequences, in the practice of copyright waqf are: 1) Waqf is null and void if the object of waqf is convicted of being unlawful; 2) The copyright that is donated can be canceled if it has not been registered; 3) A waqif copyright can be canceled if the nazhir ignores the waqif's moral rights; 4) All Copyright Waqf Pledges are timed endowments; and 5) Copyright cannot be represented for the second time. Key Word: Copyright, Waqf, Legal Consequences